PENGARUH PROPORSI KOMISARIS INDEPENDEN, FINANCIAL DISTRESS, INTENSITAS ASET TETAP, DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE (Studi pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017) - Riantami, Vivi Lestari; Triyanto, Dedik Nur (EDUTECH CONSULTANT, 2018)
This study aims to examine the effect of the proportion of independent commissioners, financial distress, fixed asset intensity, and sales growth on tax avoidance. The population in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange during 2013-2017. The number of sample companies used is 11 companies with a research year of 5 years. The total sample obtained from the reduction results using purposive sampling technique as many as 55 samples. Data analysis method uses panel data regression analysis using EViews 9.0 software by conducting several stages of testing. The results showed that financial distress had a significant effect on tax avoidance with a negative direction, while the proportion of independent commissioners, the intensity of fixed assets, and sales growth did not significantly influence tax avoidance